Study of Maggot as a Natural Decomposer of Food Waste at UTHM Cafe, Pagoh Campus - Rosmadi, Adib Afnan; Yahaya, Izat; M Z Mulyady, Muhammad Ainal Yaqin; Fazdrul Izwan, Nabil Hakimi Fazdli (Multidisciplinary Applied Research and Innovation, 2026)
Organic waste generated by institutional sources, such as university cafeterias, is a growing environmental concern due to its contribution to pollution, unpleasant odors, and ineffective disposal practices. This study investigates the potential of Hermetia illucens larvae, commonly known as Black Soldier Fly Maggots (BSFM), as a natural decomposer for food waste produced at the UTHM Pagoh Residential College cafeteria. The main objective was to determine the optimal maggot-to-waste ratio for rapid, efficient decomposition. The experiment was conducted over a two-month period, from April to early June 2025, using a home-like lab setting with one container per cycle across six experimental conditions. In Set 1, the BSFM weight was fixed at 500g while the food waste amount varied (250g, 500g, 750g). In Set 2, the food waste was fixed at 500g while the maggot weight varied (250g, 500g, 750g). Decomposition time and reduction efficiency were recorded, alongside physical observations such as waste liquefaction, odor development, and larval changes. The most effective decomposition occurred when 500g of BSFM was paired with 250g to 500g of food waste, achieving over 75% reduction within 5 to 7 days. These findings highlight BSFM as a low-cost, eco-friendly solution for small-scale organic waste management, particularly in institutional settings, and support the development of scalable composting systems that reduce waste by reusing organic materials rather than throwing them away.